Research in Personnel and Human Resources Management - Buckley, M. Ronald (Research in Personnel and Human Resources Management Series, 2023)
This book contains an Open Access chapter. Contributions include an analysis of professional touching behaviour, ideas about the state of science in HRM, processes that occur in expatriate turnover, suggestions concerning the state of human resource process research and an Open Access chapter on work-life flexibility issues